To What Extent is Collocation Knowledge Associated with Oral Proficiency? A Corpus-Based Approach to Word Association. (June 2022) - Uchihara, Takumi; Eguchi, Masaki; Clenton, Jon; Kyle, Kristopher; Saito, Kazuya
This study examined the relationship between second language (L2) learners' collocation knowledge and oral proficiency. A new approach to measuring collocation was adopted by eliciting responses through a word association task and using corpus-based measures (absolute frequency count, t -score, MI score) to analyze the degree to which stimulus words and responses were collocated. Oral proficiency was measured using human judgements and objective measures of fluency (articulation rate, silent pause ratio, filled pause ratio) and lexical richness (diversity, frequency, range). Forty Japanese university students completed a word association task and a spontaneous speaking task (picture narrative). Results indicated that speakers who used more low-frequency collocations in the word association task (i.e., lower collocation frequency scores) spoke faster with fewer silent pauses and were perceived to be more fluent. Speakers who provided more strongly associated collocations (as measured by MI) used more sophisticated lexical items and were perceived to be lexically proficient. Collocation knowledge remained as a unique predictor after the influence of learners' vocabulary size (i.e., knowledge of single-word items) was considered. These findings support the key role that collocation plays in oral proficiency and provide important insights into understanding L2 speech development from the perspective of phraseological competence.